Thermochromic biofilm from longkong peels for temperature sensors - Panupong Jaiban; Napawan In-on; Benjamaporn Injay; Punnanan Arunroj; Pharida Homket; Anucha Watcharapasorn (Results in Chemistry)
The biofilm from longkong peels was fabricated. Thermochromic pigments were added to biofilms. The FITR spectra confirmed all biofilms. The films responded to different temperatures. The R-biofilm changed from color to transparent at ∼35 °C to 42 °C. The RB-biofilm and B-biofilm changed from color to transparent ∼37 °C to 42 °C. All films were soluble in water. The result here promoted the potential for agricultural waste usage in temperature response.